Testing the effectiveness of types of bait and colors of fly traps for controlling flies at the Poultry Slaughterhouse, Mawasangka Tengah District, Central Buton Regency - Sitti Nurmayang Sari; Ramadhan Tosepu; Wa Ode Salma; Asnia Zainuddin; Syawal Kamiluddin Saptaputra; Lies Indriyani (Journal of Epidemiology and Health Science, 2024)
Background: A fly trap is a physical-mechanical method for controlling adult flies, designed to manage fly populations in areas with high fly density. Factors such as food sources, humid environmental conditions, inadequate sanitation, and substandard waste management are suspected to contribute to elevated fly populations in poultry slaughterhouses Objective: This study aims to assess the effectiveness of different bait types and trap colors in capturing flies. Method: A pure experimental design with a 3x3 factorial arrangement was employed, involving two factors: bait type and trap color. A cube-shaped fly trap, measuring 30 cm x 30 cm, was utilized. The bait types tested included chicken offal, fish offal, and shrimp, while the trap colors tested were yellow, green, and red. Data were analyzed using factorial ANOVA with SPSS software. Results: The fly trap with chicken offal bait captured 288 flies, compared to 190 flies with fish offal and 124 flies with shrimp. Among the trap colors, yellow captured 229 flies, green captured 270 flies, and red captured 103 flies. Statistical analysis revealed that bait type had a significant effect on the number of flies trapped (p = 0.032 < 0.05), as did trap color (p = 0.021 < 0.05). However, the interaction between bait type and trap color did not significantly affect the number of flies trapped (p = 0.995 > 0.05). Conclusion: The study concluded that fly traps using chicken offal bait and those colored green were most effective in capturing flies. Both bait type and trap color significantly influenced the number of flies trapped, while their combination did not have a significant impact. Keywords: bait, color, fly trap, flies, poultry slaughterhouse